Guided Inquiry Method Employing Virtual Laboratory to Improve Scientific Working Skills - Siti Juwariyah; Soepriyono Koes H; Eny Latifah (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: There are many obstacles in achieving the goals of learning physics. One of those is how students’ assumption on physics as something abstract and can not be verified by experiment, because of the unavailability of laboratory and equipment in schools. This study aims to assess if students’ scientific work skills learned through Guided Inquiry method employing Virtual Laboratory is higher than those learned through conventional method. The research used quasi-experimental research method with the Non-equivalent control group design. The data was analyzed by using ANCOVA test. The results showed that when covariable controlled the prior knowledge, students’ scientific working skill is higher with guided inquiry method employing virtual laboratory than those who learned through conventional learning.Key Words: guided inquiry, virtual labs, scientific working skill Abstrak: Banyak kendala yang harus dihadapi dalam mencapai tujuan pembelajaran fisika. Berdasarkan hasil studi pendahuluan, salah satu kendalanya adalah anggapan siswa bahwa materi fisika merupakan sesuatu yang abstrak dan tidak bisa dibuktikan kebenarannya dengan eksperimen di sekolah, karena tidak tersedianya peralatan laboratory. Telah dilakukan penelitian yang bertujuan meningkatkan keterampilan kerja ilmiah siswa yang belajar dengan pembelajaran guided Inquiry berbantuan Laboratory virtual. Metode penelitian yang di implimentasikan adalah kuasi eksperimen, dengan desain penelitian Non-equivalent control-group design. Analisis data menggunakan uji ANCOVA. Hasil penelitian menunjukkan bahwa setelah dikendalikan kovariabel pengetahuan awal, keterampilan kerja ilmiah siswa lebih tinggi pada siswa yang belajar dengan guided inquiry berbantuan laboratory virtual dibanding yang belajar dengan pembelajaran konvensionalKata kunci: Guided Inquiry, Laboratory Virtual